A collaborative access control model for e-voting systems - Ultra, John D.
We observed that distributing trust or authority, also known as Separation of Duty (SoD), is a common strategy in cryptographic voting schemes to increase the integrity and availability of its components. However, such schemes only cover a subset of the administrative activities performed in an election e.g. voter registration, voting and votes tallying. In order to maintain the overall operational integrity of an election, it is also a good idea to employ such strategy to other election administrative tasks not covered by the cryptographic voting scheme implemented on an e-voting system. To this end, we proposed a collaborative access control model which can be used for enforcing SoD on other election administrative tasks which are performed through an e-voting system.